The Secret Circuit: The Little-Known Court Where the Rules of the Information Age Unfold - Abramson, Bruce D., (Rowman & Littlefield Publishers, 2007)
Imagine a high impact, low profile, nonpartisan government institution located across the street from the White House. Imagine that it plays a central role in shaping our technology industries, in overseeing globalization, and in holding the federal government responsible for its commercial activities. Imagine that only Congress and the Supreme Court can correct its mistakes. Such an institution exists. The United States Court of Appeals for the Federal Circuit was born in the early 1980s as part of the drive to liberalize and reinvigorate the American economy. Over the past twenty-five years, it has earned its nickname as the 'patent court' by revolutionizing American patent law, but it also oversees international trade law and government business law. Taken together, its docket covers the rules guiding innovation, globalization, and much of government. Are these rules impelling the economy forward or holding it back? Are the policies we have the policies we want? How are we faring, as the economy transitions from the industrial age to the information age? What responsibility does the Federal Circuit bear in shaping America's current economic policies in these three critical areas? The Secret Circuit demystifies this Court's work and answers these questions.